Development and quality evaluation of ready to eat food from speciality rice and nendran banana - ANEESA E HRIDYA HARIDAS SURYA SURENDRAN; Dr. K.P Sudheer (Guide) (50)
Development and quality evaluation of ready to eat food from speciality rice and nendran banana
Development and quality evaluation of ready to eat food from speciality rice and nendran banana